A novel HLA‐B allele, B*58:01:12, detected in a Taiwanese volunteer bone marrow stem cell donor using sequence‐based typing method. (28th November 2012) - Yang, K. L.; Lee, S. K.; Kao, R. H.; Lin, C. L.; Lin, P. Y.
Summary Human leukocyte antigen‐B*58:01:12, a novel rare allele of HLA‐B*58:01 variant, was found in a Taiwanese volunteer bone marrow donor by SBT (sequence‐based typing) method. The DNA sequence of B*58:01:12 is identical to the sequence of B*58:01:01 in exons 2, 3 and 4 except at nucleotide position 483 where nucleotide C is substituted by T (at codon 137; GACGAT). Due to the silent point mutation, the amino acid sequence of B*58:01:12 is identical to the sequence of B*58:01:01. The HLA haplotype in association with B*58:01:12 may be deduced as A*33:03‐B*58:01:12‐DRB1*03:01. The discovery of B*58:01:12 adds further polymorphism of B*58:01 in Taiwanese population.